Household adoption of smog protective behavior: a comparison of two Chinese cities - Wei, J.; Zhu, W.; Marinova, Dora; Wang, F. (2015)
This study compares residents of two Chinese cities – one with a high risk and one with a low risk of air pollution, in terms of their smog experience, reliance on smog information sources, risk perception, attribution of responsibility and intention for adoption of protective behavior regarding smog. The results indicate that the two cities differ considerably in their smog experience, somewhat less so in reliance on smog information sources and risk perception, and very little in protective behavior. Using multiple regression analyses, the study revealed a basic chain of reaction in which demographic characteristics and location cause smog experience and smog information, smog experience and smog information cause risk perception, risk perception causes attribution of responsibility, and attribution of responsibility causes intention to adopt protective behavior. Theoretical and practical implications are discussed and recommendations for further research are suggested.